PERCEIVED LEVEL OF STRESS AMONG CASUAL DINING RESTAURANT EMPLOYEES IN KLANG VALLEY, MALAYSIA - Amran, Farah Wahida; Ghazali, Hazrina; Mohamad, Siti Fatimah (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Work-related stress is considered as the global phenomenon in many industries. Even though stress can be viewed as positive by some employees, but the majority believed work-related stress contributes more to the negative cause. Stress at the workplace also happens in the restaurant industry and stress can affect an employee’s job performance and productivity. Stress in the restaurant industry happened due to excessive working hours, shift hours, pressure or conflict with job demand and inefficient management. Albeit research on stress has been an extremely active field for many years, job-related stress in the restaurant industry was claimed had not been widely investigated. Hence, the purpose of this study is to examine the employees’ perceived stress levels in the restaurant industry, particularly in the Klang Valley area. The primary data of this study was derived from a quantitative method and strictly to Malaysian employees only. A total of 620 self-completed questionnaires were usable for data analysis. 700 questionnaires were distributed to employees who were currently working in casual dining restaurants in the Klang Valley area. Descriptive analysis was done by using the SPSS version 22. Analysis of the Perceived Stress Scale (PSS), revealed that 76.6% which accounted for 475 of respondents perceived moderate to high-stress level. This indicated employees who perceived high-stress score tend to have a higher stress level at their workplace. Additionally, results also found that most of the respondents felt stress between 1-2 times in a week with 52.7% equals to 327 of respondents. Findings obtained in this study could suggest the casual dining operators and management highlight factor that could contribute to job stress and strategize ways to minimize stress and ultimately retain their employees in the restaurant